PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN - Iskandar Iskandar (FORUM EKONOMI, 2016)
Corporate Social Responsibility (CSR) is one of concern for a company on the environment. Nowadays CSR aims to maximize profits, but also required to better accommodate the needs of society and its stakeholders. This study examined the effect of the application of corporate social responsibility to company profitability. The research sample using the 10 mining companies listed on the Stock Exchange in 2010-2013. The data used are the financial statements and annual reports issued by the company every year. The sampling technique used purposive sampling method. This study used multiple linear regression analysis. The results of this study indicate that for the year 2010-2013 for environmental development and no significant negative effect on ROA with a significance value of 0.619, partnership and not significant positive effect on ROA with a significance value of 0.162 and welfare of employees and a significant negative effect on ROA value significance of 0.039.Keyword: Corporate Social Responsibility, Profitabilitas.